Disconnected Lifelines: The Crisis of Interoperability in Emergency Medical Services, Technicians, and Specialists - Isra Hassan Hussain Alghafly, Mansour Ali Mansour Johali, Hussain Ali Jubran Shafei, Osama Bin Jadih Mshhour, Abdulaziz Saeed Almutairi, Sultan Murdi Almutairi, Ahmed Fari Almutairi, Abdulaziz Mastour Almutairi (Journal of International Crisis and Risk Communication Research, 2024)
The interoperability crisis in Emergency Medical Services (EMS), technicians, and specialists creates significant barriers to effective emergency responses. Issues such as incompatible technologies, lack of standardized protocols, and organizational misalignment result in delayed care, miscommunication, and compromised patient safety. Addressing these challenges requires integrating technological solutions, standardized frameworks, and collaborative policies to ensure seamless communication and data sharing. Aim of Work: This study aims to analyze the root causes and implications of interoperability challenges in EMS and healthcare systems, emphasizing the roles of EMS personnel, technicians, and specialists. It seeks to propose frameworks and technological innovations to enhance communication, coordination, and data-sharing efficiency, ultimately improving emergency response outcomes.